STUDI KASUS KEBIJAKAN PENDIDIKAN GLOBAL : KAJIAN OECD, UNESCO, WORLD BANK TERHADAP KEBIJAKAN PENDIDIKAN DI INDONESIA - Luthfanie, Dhika; Hudaya, Akhmad; Dian Suandri, Andri; Duryat, Masduki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The globalization of education encourages policy convergence through the influence of international institutions. This study aims to analyze the Case Study of Global Education Policy: Studies by the OECD, UNESCO, and the World Bank on Education Policy in Indonesia. The method used is a literature study with a comparative qualitative approach. The results of the study indicate that Indonesian education policy is influenced by global standards such as PISA, SDGs, and efficiency-based approaches. Comparison of education between countries in the context of a case study of global education policy is a very important study to understand how the process of globalization influences the direction, structure, and practices of education systems in various countries. Globalization encourages countries to adopt international education standards, such as strengthening global literacy, improving the quality of human resources, and implementing universal education quality indicators. In addition, globalization also opens up space for the exchange of best practices between countries as an effort to increase educational competitiveness at the global level. Through a comparative education approach, this study seeks to identify similarities, differences, and forms of adaptation of education policies implemented by various countries in response to global demands as well as diverse local needs. This approach allows researchers to understand how global education policies are interpreted and implemented according to the social, cultural, economic, and political contexts of each country. With a comparative approach, this research is expected to provide strategic and practical recommendations for policy makers in developing an adaptive, inclusive, and internationally competitive education system without ignoring local values ​​and national development